Anthropological differentiation of some West African tribes - Stolarczyk, Henryk (Anthropological Review, 1978)
The present paper concerns anthropometric and somatoscopic materials relating to the three most numerous in West Africa ethnic groups: Hausa, Yoruba, and Ibo. The material comprises observations on 181 males and 120 females collected in Niger and Nigeria in 1975 and in recent years at the College of Polish Language for Foreigners in Łódź. Comparing averages of some anthropometric and somatoscopic traits one can see clear distinction between Hausa and two remaining ethnic groups. It is particularly apparent in head measurements (g-op, eu-eu), face breadth (zy-zy) and nose size (n-sn, al-al). Moreover, considerable differences occur in a number of quotient indices (cephalic index, head height-length index, and breadth-length index, morphological face index, nasal index) and in skin colour. Tribes Yoruba and Ibo consist of morphologically similar individuals. Larger differences between tribes can be seen in head breadth, cephalic index and skin colour. Analysis of material from the angle of racial composition employing morphological comparative method also points toward high anthropological differentiation of people belonging to tribes in question. Racial composition of Hausa people being characterised by striking prevalence of equatorial and sudanese components and complete lack of pygmoid component differs strongly from racial characteristics of Yoruba and Ibo in which considerable role is played by pygmoid component. Obviously, the is a correlation between anthropometry/somatoscopy and racial composition evaluation as the latter is based indirectly on observations of same characters.